Dampak Kepuasan dan Motivasi Kerja terhadap Dinamika Perilaku Organisasi Karyawan UD Esa Jaya Surabaya - Adinda Eka Rahmawati; Sentot Imam Wahjono (Pusat Riset dan Inovasi Nasional, 2025)
Successful organizations rely not only on physical resources and technology, but also on human resources, which play a key role in driving organizational processes. One of the key factors that influence the quality and effectiveness of employee performance is job satisfaction and motivation. This study aims to evaluate the influence of job satisfaction and motivation on the organizational behavior dynamics of employees at UD Esa Jaya. The research method used is qualitative with an economic approach. Data collection was conducted through observation and in-depth interviews with employees and management. The data obtained were analyzed using qualitative descriptive methods to explore the relationship between job satisfaction, motivation, and organizational behavior. The results of the study indicate that job satisfaction and motivation have a significant impact on employee behavior, including in terms of productivity, loyalty, and social interaction in the workplace. These findings provide important contributions to management in developing policies that can enhance job satisfaction and motivation, thereby creating a more efficient and conducive organizational environment.